Analysis of Difficulties in Speaking Arabic Among Students of Traditional Islamic Boarding School (Salaf) - Fityatul Mujahidah Lubis (Universitas Muhammadiyah Enrekang, 2023)
Practicing spoken Arabic is not an easy task. Collaboration with various parties is required, one of which is the school teacher. The primary issue with the Salaf Islamic Boarding School is that a significant number of students struggle with spoken Arabic, although they are capable of reading Arabic texts without diacritical marks. Unfortunately, research on this topic remains highly limited. To address this gap, this study employs exploratory qualitative methods to analyze the challenges faced by Salaf students in speaking Arabic. Data collection was conducted through in-depth and open interviews, involving five teachers from the Salaf Islamic Boarding School and ten students. From this study, several findings emerged, including the following difficulties experienced by students in speaking Arabic: (1) a lack of vocabulary, (2) a lack of motivation, (3) hesitancy to speak due to fear of making mistakes, and (4) feeling embarrassed when speaking Arabic. It is hoped that this research will help identify the difficulties faced by students in speaking Arabic and provide appropriate solutions to further enhance their speaking skills.